Rare and Undiagnosed Disease: A Learning Program for Nurses and Midwives - Sue Baker; Kaila Stevens; Dale Pugh (Nursing Reports)
This paper presents a newly developed online learning program currently designed to meet the learning objectives of nurses and midwives and rare and undiagnosed disease. Background/Objectives: This paper will also introduce the Global Nursing Network for Rare Disease and its role and commitment in supporting nurses and midwives in the identification of rare disease and the delivery of appropriate care and interventions to care for people living with rare and undiagnosed disease. Globally, nurses and midwives are often the first healthcare provider a patient will engage with. Combined with the estimated 300 million living with a rare disease across the globe, nurses and midwives are well positioned when assessing patients to have adequate awareness and suspicion to consider the presence and impact of rare disease. To enable this awareness and knowledge to ensure timely assessment and referrals, specific knowledge is required. There is a current paucity of learning programs about rare and undiagnosed disease specifically for nurses and midwives. Methods: The proposed learning program comprises seven modules designed to address the learning needs of novice to expert nurses and midwives from across the globe. Increased knowledge will in turn increase awareness and confidence to inform decision-making for patients presenting with undiagnosed signs and symptoms by ‘thinking rare’. Results: The proposed learning program comprises seven modules and a number of individual lessons which will be suitable for the needs of novice to expert nurses and midwives from across the globe.